1998
DOI: 10.1002/(sici)1099-0844(1998120)16:4<227::aid-cbf787>3.0.co;2-m
|View full text |Cite
|
Sign up to set email alerts
|

Blood plasma levels of lipoperoxides, glutathione peroxidase, beta carotene, vitamin A and E in women with habitual abortion

Abstract: The plasma levels of lipoperoxides, glutathione peroxidase (GSH-Px), reduced glutathione (GSH), beta carotene, vitamin A, E, some plasma biochemical and blood haematological parameters were investigated in 40 women with habitual abortion (HA) and controls. The levels of GSH, vitamin A, E and beta carotene were significantly lower in women with HA than in controls. However, the plasma levels of lipid peroxidation, alkaline phosphatase (ALP), glucose and blood haemoglobin were significantly higher in HA than in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
20
1

Year Published

2000
2000
2019
2019

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 82 publications
(23 citation statements)
references
References 18 publications
(20 reference statements)
2
20
1
Order By: Relevance
“…Safronova et al [44] found an elevated production of toxic oxygen species in the granulocytes of patients with a history of RPL versus control subjects with normal reproductive function. Increased lipid peroxidation and reduced antioxidant levels in women with a history of abortions were reported by Şimşek et al [45], supporting the concept that OS plays a central role in the etiopathogenesis of RPL. Inflammatory immune responses also are a key factor in reproductive failures, such as in multiple implantation failures, early pregnancy loss, and RPL, because cellular immune responses, especially those mediated by natural killer and T cells, are often dysregulated in these conditions [46].…”
Section: Oxidative Stress and Pregnancy-related Disorderssupporting
confidence: 65%
“…Safronova et al [44] found an elevated production of toxic oxygen species in the granulocytes of patients with a history of RPL versus control subjects with normal reproductive function. Increased lipid peroxidation and reduced antioxidant levels in women with a history of abortions were reported by Şimşek et al [45], supporting the concept that OS plays a central role in the etiopathogenesis of RPL. Inflammatory immune responses also are a key factor in reproductive failures, such as in multiple implantation failures, early pregnancy loss, and RPL, because cellular immune responses, especially those mediated by natural killer and T cells, are often dysregulated in these conditions [46].…”
Section: Oxidative Stress and Pregnancy-related Disorderssupporting
confidence: 65%
“…in our study showed the highest median values of LPx, found in the group of patients with spontaneous abortions (the group S -48.03 pmoL/mg Hgb), while the control group of healthy pregnancies had the lowest median values of LPx (the group N -26.06 pmoL/mg Hgb) ( Table 2). A research conducted by Ozakaya et al 23 as well as by Simşek et al 24 yielded the same results. The increase of lipid peroxidation levels immediately before the onset of a spontaneous abortion and significantly lower values following the abortion were measured in the research by Sane et al 25 .…”
Section: Discussionsupporting
confidence: 58%
“…In keeping with this idea, plasma lipid peroxides and GSH have been observed in increased levels, in addition to decreased levels of vitamin E and β-carotene in patients with RPL [167]. Furthermore, markedly increased levels of GSH have also been found in the plasma of women with a history of RPL, indicating a response to augmented OS [168].…”
Section: Pregnancy Complicationsmentioning
confidence: 96%